1993
DOI: 10.1063/1.109671
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond ellipsometric study of nonequilibrium carrier dynamics in Ge and epitaxial Si1−xGex

Abstract: The time-resolved, above-gap optical response of optically thick Si1−xGex alloys to carrier injection by a femtosecond pump pulse is measured across the entire compositional range (0≤x≤1) using a novel femtosecond ellipsometric technique which clearly distinguishes the real and imaginary parts of the time-varying dielectric function ε1(t)+iε2(t). The results are modeled microscopically in terms of the Drude contribution from a diffusing hot electron-hole plasma, augmented by transient-induced absorption from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In practice, the number of non-equilibrium phonons has been measured through the Raman scattering method, demonstrating the existence of non-equilibrium phonons generated by hot carriers [20][21][22][23][24] . Hu et al used the van Driel system [23][24][25] to study the change of carrier concentration, lattice temperature with the pulse duration, and found that carrier density and lattice temperature at the surface of semiconductor rise with the increase of pulse duration, which is in good agreement with the experimental results [17,26] . However, the dynamical process inside the semiconductor is less investigated [27] , and it will be investigated in present work.…”
Section: Introductionsupporting
confidence: 78%
“…In practice, the number of non-equilibrium phonons has been measured through the Raman scattering method, demonstrating the existence of non-equilibrium phonons generated by hot carriers [20][21][22][23][24] . Hu et al used the van Driel system [23][24][25] to study the change of carrier concentration, lattice temperature with the pulse duration, and found that carrier density and lattice temperature at the surface of semiconductor rise with the increase of pulse duration, which is in good agreement with the experimental results [17,26] . However, the dynamical process inside the semiconductor is less investigated [27] , and it will be investigated in present work.…”
Section: Introductionsupporting
confidence: 78%
“…Once ⌬E x is known, the change of the Ge dielectric function, ϭ 1 ϩi 2 , can be calculated from the energy dependence of the dielectric function 23 as ⌬ 1,2 ϭ(‫ץ‬ 1,2 /‫ץ‬E)⌬E x . 24 The obtained change in ⑀ of bulk Ge has been introduced in the effective-medium formulation 25 to obtain the variation in the dielectric function of the composite medium ͑i.e., nanoparticles and matrix͒ and consequently the nanoparticle reflectivity and transmissivity changes. Figure 7 shows the calculated differential reflectivity and transmissivity spectra, assuming that all the photogenerated electrons are relaxed to the bottom of the L valleys ͑i.e., we consider pump-probe delays larger than ϳ4 ps͒.…”
Section: Modeling and Discussionmentioning
confidence: 99%
“…[7], we obtained DE g values of the order of 30 meV. This reduction of the energy gap produces a variation in the dielectric function of the nanoparticles which can be evaluated as [9] De 1Y 2 de 1Y 2 adE DE g .…”
Section: Transient Effectsmentioning
confidence: 99%
“…± ± Presence of a structure due to the plasma resonance, whose effects on the dielectric function can be expressed via a Drude-Lorentz formulation [9].…”
Section: Transient Effectsmentioning
confidence: 99%